2017
DOI: 10.1007/s10815-017-1032-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between fatty acid index and in vitro fertilization outcomes

Abstract: No correlation was observed between omega-3 index and IVF outcomes. Elevated erythrocyte EA index, the major trans fatty acid commonly consumed in hydrogenated oils, margarine, and fried foods, was negatively correlated with number of usable blastocysts and embryos, blastocyst conversion, and fertilization rate. Our findings suggest preliminary evidence that trans fat may be negatively associated with IVF outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Standardized alimentary supplementation of omega-3-fatty acids before and during an in vitro fertilization therapy so far has not been subject of a well-designed randomized prospective study. Just few small, prospective cohort studies have examined the relationship between serum omega-3-fatty acid levels and IVF-success with conflicting results [16][17][18][19][20]. One of the first approaches to study the correlation of omega-3-fatty acid supplementation and the probability of a pregnancy is the PREPARE-trial by Kermack and co-workers [15], which has not been finished yet.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized alimentary supplementation of omega-3-fatty acids before and during an in vitro fertilization therapy so far has not been subject of a well-designed randomized prospective study. Just few small, prospective cohort studies have examined the relationship between serum omega-3-fatty acid levels and IVF-success with conflicting results [16][17][18][19][20]. One of the first approaches to study the correlation of omega-3-fatty acid supplementation and the probability of a pregnancy is the PREPARE-trial by Kermack and co-workers [15], which has not been finished yet.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol serves as a substrate for the synthesis of the plasma membrane and steroid hormones indispensable for the growth of activated steroidogenic cells (DeAngelis, Roy‐O'Reilly, & Rodriguez, ). Meanwhile, fatty acids, as crucial components of membrane lipids and substrates for prostaglandin synthesis, function in cell division, and oocyte maturation (Eskew et al, ). There remains an interesting area of cholesterol and fatty acid metabolic pathways and their impact on human reproductive health.…”
Section: Discussionmentioning
confidence: 99%
“…No correlation between omega-3 PUFA index and IVF outcomes, such as number of oocytes retrieved, embryo grade or clinical pregnancy, was found in another small study (n = 60) (Eskew et al, 2017). Mirabi et al (2017) measured serum and follicular fluid level of fatty acids in 105 women undergoing IVF.…”
Section: Omega-3 Pufas In Assisted Reproductive Technologiesmentioning
confidence: 96%
“…It is unclear why studies in IVF have yielded conflicting results on the relationship between PUFA intake and IVF outcomes, but it may be due, in part, to the combination of a small number of cycles in each study and the variability of studies. In total, five studies (556 cycles) reported a clinical outcome of IVF: two studies showed a positive effect of omega-3 PUFAs, especially EPA, on clinical pregnancy (Mirabi et al, 2017;Chiu et al, 2018), one found no correlation (Eskew et al, 2017), and one found a negative effect of ALA (Jungheim et al, 2011); however, in a larger follow-up study from the same group, no detrimental effect was found nor was a correlation found between PUFAs and the chance of becoming pregnant, although a higher ratio of linoleic acid-ALA increased this chance (Jungheim et al, 2013). Marked differences exist between the studies.…”
Section: Yesmentioning
confidence: 99%
See 1 more Smart Citation